Early-Life Temperamental Differences as Longitudinal Predictors of Unintentional Injuries - Ksinan, Albert J; Dalecká, Andrea; Kukla, Lubomír; Pikhart, Hynek; Bobák, Martin (Journal of pediatric psychology, 2024)
OBJECTIVE: Unintentional injuries are the leading cause of hospitalization and death among children. Compared to environmental factors, less attention in injury preventive efforts has been paid to how individual characteristics relate to the risk of injury. Using a large prospective cohort, the current study assessed the longitudinal impact of early-life temperament on the cumulative number of injuries until mid-adolescence. METHODS: The data came from the European Longitudinal Study of Pregnancy and Childhood (ELSPAC-CZ). Temperament was evaluated by mothers when children were 3 years old (N = 3,545). The main outcome was the pediatrician-reported sum of child's injuries from age 3 to 15 (seven timepoints). Latent profile analysis (LPA) was used to determine classes based on temperamental dimensions and then extended to a mixture model with a distal count outcome. The covariates included maternal conflict and attachment, sex, family structure, and maternal education. RESULTS: The LPA determined the existence of three classes: shy children (8.1% of the sample; lowest activity/highest shyness), outgoing children (50.8%; highest activity/lowest shyness), and average: children (41.1%; middle values). Results from a mixture model showed that the outgoing temperament was associated with the highest longitudinal risk for injuries, as both average children (IRR = 0.89 [0.80, 0.99]), and the shy children (IRR = 0.80 [0.68, 0.95]) had lower risk. CONCLUSIONS: Early childhood temperamental differences can have long-term effects on injury risk. Highly active children showed the highest risk for future injuries, suggesting that these characteristics make them more likely to be involved in novel and potentially dangerous situations.
Keywords: longitudinal; Pregnancy; Humans; Longitudinal Studies; injury; dítě; prevention; Child; Female; rizikové faktory; temperament; latent profile analysis; lidé; Temperament; Mothers; předškolní dítě; ženské pohlaví; longitudinální studie; personality; Adolescent; těhotenství; matky; prospektivní studie; Child, Preschool; mladiství; Risk Factors; Prospective Studies